Current Status of mTOR Inhibitors as Novel Therapeutic Agents - Laxmianarayana Bairy Kurady (Journal of Global Pharma Technology, 2017)
Mammalian target of rapamycin (mTOR) is a PI3K (phosphatidylinositol-3-kinase)-related kinase, via two distinct forms – mTOR complex 1 (mTORC1) and mTORC2 coordinates various extracellular and intracellular signals like growth factors, nutrients, amino acids, energy levels in order to achieve optimum cell growth. mTORC1 regulates protein synthesis, lipid biogenesis, oxygen homeostasis, proliferation, autophagy; mTORC2 plays role in cell survival. Since this pathway controls major cellular processes, its dysregulation is associated with pathological conditions like cancer, obesity, type 2 diabetes mellitus. Rapamycin, a naturally occurring mTOR inhibitor, along with synthetically derived compounds of rapamycin – rapamycin analogs (rapalogs), produced by chemical modification of parent drug have achieved clinical success in certain tumor subtypes. Rapalogs have shown their own limitations due to development of resistance and activation of feedback pathways, focusing on the need for efficient mTOR inhibition. In this regard, mTORC1/mTORC2 (mTOR Kinase) inhibitors and dual mTOR/PI3K inhibitors have shown promising results in various in-vitro tumor models, and are currently in phase I/II of clinical trials. With the better understanding of dynamics of mTOR signaling pathway and its function in tumor microenvironment, mTOR inhibitors may provide a good alternative against advanced and refractory cancers.Keywords: Rapamycin, mTOR, Tuberous sclerosis complex, PI3K, AKT, Rapalogs, Everolimus.